The impact of robotification on the financial situation of microenterprises: Evidence from the financial services sector in Poland - Maciej Cieślukowski; Przemysław Garsztka; Beata Zyznarska-Dworczak (Risks, 2022)
The automation of manufacturing processes as a result of the Fourth Industrial Revolution, rendered faster under the influence of the COVID-19 pandemic, leads to a question as to whether small enterprises, and in particular microenterprises, will still be financially self-sufficient. The literature on the subject so far has not provided an answer to this question, and limited access to financial data concerning microenterprises, as well as data on the robotification of labour in these companies, leads to this problem becoming a research niche. Therefore, this paper aims to assess the attractiveness of the operation of microenterprises that provide financial advisory services in the situation of replacing human labour with robots. For that purpose, we performed a simulation of the state of the microenterprise before and after introducing the robotification of services, taking into account the extra tax on robotification. The findings indicate that anticipating the improvement of financial results following the automation of financial services requires taking into account the replaceability of employees in a particular unit, the form of acquiring a robot and a potential increase in the tax burden (with a tax compensating for the lost state income).
Keywords: 330; automation; financial advisory services; financial forecasting methods; financial risk; microenterprises; robots